Creating Functional Artificial Proteins - Razeghifard, Reza; Wallace, Brett B.; Pace, Ron J.; Wydrzynski, Tom (Current Protein and Peptide Science, 2007)
Much is now known about how protein folding occurs, through the sequence analysis of proteins of known folding geometry and the sequence/structural analysis of proteins and their mutants. This has allowed not only the modification of natural proteins but also the construction of de novo polypeptides with predictable folding patterns. Structure/ function analysis of natural proteins is used to construct derived versions that retain a degree of biological activity. The constructed versions made of either natural or artificial sequences contain critical residues for activity such as receptor binding. In some cases, the functionality is introduced by incorporating binding sites for other elements, such as organic cofactors or transition metals, into the protein scaffold. While these modified proteins can mimic the function of natural proteins, they can also be constructed to have novel activities. Recently engineered photoactive proteins are good examples of such systems in which a light-induced electron transfer can be established in normally light-insensitive proteins. The present review covers some aspects of protein design that have been used to investigate protein receptor binding, cofactor binding and biological electron transfer.
Keywords: reaction center